2022
DOI: 10.1186/s13063-022-06626-w
|View full text |Cite|
|
Sign up to set email alerts
|

G-CuP: the effect of a forced oral glucose intake on alcohol craving and mesolimbic cue reactivity in alcohol dependence—study protocol of a randomized, double-blind, placebo-controlled crossover study

Abstract: Background Multiple studies indicate that a lower plasma level of the acetylated form of the appetite-regulating hormone ghrelin and higher plasma levels of insulin lead to a reduction in subjective alcohol craving and a reduced mesolimbic cue reactivity in functional magnetic resonance imaging (fMRI) when being exposed to alcohol-associated stimuli. The ghrelin level can physiologically be reduced by the induction of stomach distension and the ingestion of glucose or lipids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Patrick Bach.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Patrick Bach.…”
mentioning
confidence: 99%